Higher levels of plasmatic saturated fatty acid were significantly associated with liver fibrosis in HIV mono-infection: A case-control study - Cristiane Fonseca de Almeida; Wilza Arantes Ferreira Peres; Paula Simplício da Silva; Claudia Santos de Aguiar Cardoso; Michelle Morata de Andrade; Julio Castro-Alves; Marcel de Souza Borges Quintana; Marina Campos Araujo; Karla Yasmin Dias Fraga; Julliana Antunes Cormack; Ronaldo Ismerio Moreira; Sandra W. Cardoso; et al. (Metabolism Open)
Background: The relationship between plasmatic fatty acid (FA) composition and liver fibrosis remains scarce in people living with HIV/AIDS (PLWHA). We aimed to evaluate the association of plasmatic FAs and liver fibrosis in HIV mono-infected individuals. Methods: This case-control study included PLWHA with liver fibrosis (cases) and randomly selected subjects without fibrosis (controls) from the PROSPEC-HIV study (NCT02542020). Participants with viral hepatitis, abusive alcohol consumption and lipid supplements use were excluded. Liver fibrosis was defined using transient elastography (TE) by liver stiffness measurement (LSM) ≥ 7.1 kPa or ≥ 6.2 kPa with M or XL probe, respectively. All HIV mono-infected participants with liver fibrosis identified at the baseline PROSPEC-HIV visit were included. Controls (1:1) were randomly selected among those HIV mono-infected participants without liver fibrosis. Plasmatic FA profile, dietary lipid intake, anthropometric measures, and blood samples were assessed. Plasmatic fatty acid was analyzed using gas chromatography and intake of fats lipids were assessed by two 24-h dietary recall (24-HDR). Multivariate logistic regression models adjusted by age, sex at birth and duration of antiretroviral therapy (ART) were performed. Results: A total of 142 participants (71 cases and 71 controls) [62 % female, median age = 46 (IQR, 37–53) years, 14.8 % with diabetes, median CD4 count = 655 cells/mm3, 96.5 % under ART] were included. Higher percentages of plasmatic palmitc acid (16:0) and saturated fatty acids (SFA) were observed in participants with liver fibrosis (cases) compared to those without (controls). Presence of higher percentage of plasmatic palmitc acid (16:0) was associated with an increased odds for liver fibrosis [adjusted OR = 1.23 (95%CI 1.04–1.46); p = 0.02] in multivariate models. Conclusion: This study showed the potential role of the plasmatic FA composition in the pathogenesis of liver fibrosis in PLWHA.